Stability and Change in Fatty Acids Composition of Soybean, Corn, and Sunflower Oils during the Heating Process - Ammar Cherif; Amor Slama (Journal of Food Quality)
This work has been undertaken to investigate the effect of heat treatment on the edible oils (soybean, sunflower, and corn) used in frying and cooking, in particular on the fatty acid composition. The heating process was maintained at 150, 180, 210, and 240°C. At each temperature, the variation of the fatty acid composition was determined after 12, 24, 36, 48, and 60 h of treatment by using an improved analytical gas chromatography method. This study showed that the oils, which had undergone a temperature of 150 to 180°C, kept some thermal stability and preserved their fatty acid composition at different treatment periods. At the temperature (180°C), two new fatty acids (C8:0 and C12:0) appeared, which could be explained by the transformation of the other fatty acids during the heating process by different chemical reactions. However, the composition of the three oils was significantly affected at 210°C and 240°C. Two trans-fatty acids (C18:1 9t and C18:2tt) were generated proportionally to heat treatment during the heating process for the three oils, providing information on their oxidative state. The results showed that sunflower oil was most affected by the heating temperature than soybean and corn oil. Therefore, more attention should be paid to the heat treatment used and the heating period to preserve the quality of edible oils.